Der Briefwechsel - Twardowski, Kazimierz; Meinong, Alexius (De Gruyter, 2016)
The correspondence between Meinong and Kazimierz Twardowski highlights the relationship between two philosophers who influenced the history of philosophy and psychology in Austria and Poland. The two correspondents discuss, among other things, their epistemological approach and the university politics of their times. In addition, there is an extensive introduction that places the correspondence in its proper historical and philosophical context.
English